SISTEM INFORMASI PENERIMAAN CALON TENAGA KERJA INDONESIA PDA PT DEWI PENGAYOM BANGSA KABUPATEN PATI - Ramanda, Febri; Shodiq, Muhammad; Nur, Delyardi (Jurnal Informatika Medis, 2023)
One form of service in PT Dewi protector Nations Pati regency receive prospective workers to some of Taiwan, Hongkong, Singapore often have difficulty including data management is still done manually, the amount of data they accumulate, requiring a lot of space to save the files prospective migrants and the length of the search data. The system developed is expected to address the various issues of labor recruitment Indonesia. The system is designed with modeling UML (Unified Modeling Language) and programming languages PHP. The result of this design produces Candidate Information System Acceptance Indonesian Workers at PT Dewi protector Nation Pati regency.